2018
DOI: 10.1099/ijsem.0.002486
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and symbiotic effectiveness of Bradyrhizobium strains nodulating selected annual grain legumes growing in Ethiopia

Abstract: Vigna unguiculata, Vigna radiata and Arachis hypogaea growing in Ethiopia are nodulated by a genetically diverse group of Bradyrhizobium strains. To determine the genetic identity and symbiotic effectiveness of these bacteria, a collection of 36 test strains originating from the root nodules of the three hosts was investigated using multilocus sequence analyses (MLSA) of core genes including 16S rRNA, recA, glnII, gyrB, atpD and dnaK. Sequence analysis of nodA and nifH genes along with tests for symbiotic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…The analysis of nodA , nodC, as well as nifD and nifH gene sequences revealed a high level of diversity within the genus Bradyrhizobium [ 21 , 60 , 70 , 82 , 114 , 126 , 127 , 128 , 129 , 130 , 131 ]. In recently published phylogenies of nodA and nifD symbiotic genes, Bradyrhizobium strains formed 16 major groups, referred to as Clade I–Clade XVI [ 28 ].…”
Section: Phylogeny Of Symbiotic Loci Of Genisteae-nodulating mentioning
confidence: 99%
“…The analysis of nodA , nodC, as well as nifD and nifH gene sequences revealed a high level of diversity within the genus Bradyrhizobium [ 21 , 60 , 70 , 82 , 114 , 126 , 127 , 128 , 129 , 130 , 131 ]. In recently published phylogenies of nodA and nifD symbiotic genes, Bradyrhizobium strains formed 16 major groups, referred to as Clade I–Clade XVI [ 28 ].…”
Section: Phylogeny Of Symbiotic Loci Of Genisteae-nodulating mentioning
confidence: 99%
“…In the case of housekeeping genes, their similarity values for the tested strains were much lower compared to those of the 16S rRNA gene sequences, which were identical or almost identical. However, it was earlier found that 16S rDNA could be identical among closely related species from the genus Bradyrhizobium (Degefu et al 2018). Based on the highlevel similarity of housekeeping gene sequences and the independent phylogenetic position of the tested strains along with the B. algeriense RST89 T , recovered by MLSA, it is reasonable to regard B. algeriense as the closest phylogenetic neighbor of the tested isolates.…”
Section: Discussionmentioning
confidence: 92%
“…Bacteria in the genus Bradyrhizobium have symbiotic genes displaying a high level of diversity and a different evolutionary history from their housekeeping genes, which suggests their acquisition by lateral gene transfer (LGT) (Menna and Hungria 2011;Lindström et al 2015;Hungria et al 2015). It has been reported that sequence analysis of nodA and nifH genes can be useful to examine the symbiotic diversity of Bradyrhizobium strains and elucidate the role of LGT in inheritance of the symbiotic loci (Degefu et al 2018). The phylogenetic studies of nodA and nifH symbiotic genes, which revealed 16 major clades in the genus Bradyrhizobium, have facilitated the development of the phylogeographic framework for this group of bacteria (Beukes et al 2016;Stępkowski et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The few studies focusing on “cowpea group” rhizobia (from agricultural plants) spanned the countries of Botswana and South Africa (Steenkamp et al, 2008 ), Botswana, South Africa, and Ghana (Pule-Meulenberg et al, 2010 ), Senegal (Wade et al, 2014 ), Namibia and Angola (Grönemeyer et al, 2014 ), Ghana and South Africa (Puozaa et al, 2017 ), Mozambique (Chidebe et al, 2018 ), Kenya (Ndungu et al, 2018 ), and Ethiopia (Degefu et al, 2018 ). Their main findings were in general agreement: First, almost all detected genotypes presumably represented yet unknown species (Steenkamp et al, 2008 ; Grönemeyer et al, 2014 ; Wade et al, 2014 ; Degefu et al, 2018 ). Second, genotype occurrence strongly relied on the geographic location (Steenkamp et al, 2008 ; Pule-Meulenberg et al, 2010 ; Grönemeyer et al, 2014 ; Wade et al, 2014 ).…”
Section: Putative Bradyrhizobium Diversity To Be Umentioning
confidence: 99%